Adventures in Ethnicity: Consuming Performances of Cultural Identity in Winnipeg’s Folklorama - Thoroski, Cynthia (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1997)
The representation of ethnicity within mainstream multicultural festivals tends to commodify ethnic identity within homogenized and simplified frameworks which ease consumption by mass audiences. “Adventures in Ethnicity” examines some of the cultural politics implicit in this brand of “fast food multiculturalism” and the ways in which large-scale multicultural festivals decontextualize, neutralize and remobilize representations of “ethnic authenticity” to market cultural identities as symbolic products. A secondary focus of discussion examines Winnipeg’s Folklorama as a case study in possibly resistant and deferential strategies within mainstream multicultural festivals’ appropriation of ethnic identities. A special emphasis is placed on the implicit cross-coding of public performance and displays of material culture to create a potentially subversive critique of large-scale multicultural festivals, their products and their consumers.